2017
DOI: 10.7150/ijbs.16951
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Secreted from Human-Induced Pluripotent Stem Cell-Derived Mesenchymal Stem Cells Prevent Osteonecrosis of the Femoral Head by Promoting Angiogenesis

Abstract: Background: Local ischemia is the main pathological performance in osteonecrosis of the femoral head (ONFH). There is currently no effective therapy to promote angiogenesis in the femoral head. Recent studies revealed that exosomes secreted by induced pluripotent stem cell-derived mesenchymal stem cells (iPS-MSC-Exos) have great therapeutic potential in ischemic tissues, but whether they could promote angiogenesis in ONFH has not been reported, and little is known regarding the underlying mechanism.Methods: iP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
186
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 217 publications
(191 citation statements)
references
References 41 publications
2
186
0
3
Order By: Relevance
“…It has been reported that the major challenge after graft implantation is the maintenance of cell viability in the graft core, which depends on rapid angiogenesis within the tissue‐engineered implants . Researchers have demonstrated that exosomes can stimulate angiogenesis in bone, which is an important mechanism for stimulating bone regeneration . Consistent with previous studies, we found that both dBMSC‐exos and nBMSC‐exos could enhance the angiogenic activity of HUVECs and promote neovascularization in rat calvarial defects.…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported that the major challenge after graft implantation is the maintenance of cell viability in the graft core, which depends on rapid angiogenesis within the tissue‐engineered implants . Researchers have demonstrated that exosomes can stimulate angiogenesis in bone, which is an important mechanism for stimulating bone regeneration . Consistent with previous studies, we found that both dBMSC‐exos and nBMSC‐exos could enhance the angiogenic activity of HUVECs and promote neovascularization in rat calvarial defects.…”
Section: Discussionsupporting
confidence: 90%
“…Targeting these exosomes, which act as important communicators between cells, may emerge as a new therapeutic approach for osteoporosis (Liu et al., 2017; Long et al., 2017; Nakano et al., 2016). In this study, we used antagomiR‐31a‐5p, which was injected into the bone marrow microenvironment, to decrease miR‐31a‐5p expression in the bone marrow microenvironment of osteoporotic rats.…”
Section: Discussionmentioning
confidence: 99%
“…We found that iMSCs-EVs alleviated hind-limb ischemic injury [27], hepatic IR injury [42] and osteoarthritis [43]. Moreover, iMSCs-EVs also prevented osteonecrosis of the femoral head [44] and enhanced bone regeneration [45,46] and cutaneous wound healing [47]. Based on these findings, we used iMSCs-EVs particles administered at the abovementioned concentration as a positive control in experiments designed to detect the effects of the USCs-EVs on ischemic hind-limb repair.…”
Section: Discussionmentioning
confidence: 99%